BINARY OPPOSITION AS THE CHARACTERIZATION IN CASEY WATSON’S A BOY WITHOUT HOPE - Afifuddin, Muzakki; Auliana, Azka (Annual International Conferences on Language, Literature, and Media, 2021)
This study aims at examining the characterization of two main characters in Casey Watson’s A Boy without Hope (2018) through the theory of binary opposition. Binary opposition is one of the theories of structuralism developed by Levi Strauss, which roots from the theory of semiotics introduced by Saussure. Aside from discovering the differences in the way the main characters are characterized, this study uses the plot of the story to discover whether the binary opposing characterization is maintained along the plot of the story. This study thus finds that binary opposition plays a significant role in character development throughout the plot of the story. However, this study limits its action only in observing the relationship between characterization and plot of the story, therefore, explorations on the paradigmatic viewpoints of the story and certain correlation among other intrinsic aspects and extrinsic aspects are suggested.